Невская битва - Коваленко Денис Леонидович (Серия "Великие битвы России", 2021)
Экземпляры: ф.1 (20220606) / Инвентарный номер: 62289 / Цена: / Сис.шифр: 63.3(2)43 / Авт.знак: К 56 / ГРНТИ: 03.23.25 / ББК: 63.3(2)43